From Spiritual Leadership to Functional Leadership: A Qualitative Single-Case Study of Authority Mediation in Jamaah Wirid Khusus Nahdlatul Wathan, Lombok - Muhammad Aska Irfani; Harapandi Dahri (Living Islam: Journal of Islamic Discourses, 2025)
This study responds to the tendency of tariqah studies in Indonesia that highlight elite figures and institutions, thereby neglecting how congregations maintain the continuity of Sufi practice in everyday life. By taking the case of Jamaah Wirid Khusus Nahdlatul Wathan (JWK-NW) in Lombok, this study examines how ritual authority, social relevance, and ethical productivity continue to operate when there is no doctrinal successor murshid, because TGKH Muhammad Zainuddin Abdul Madjid is positioned as the first and last murshid. The study uses a qualitative single-case design based on fieldwork (October to November 2023) through semi-structured interviews, non-participant observation of Hiziban, wirid, and muzakarah, as well as document analysis (Hizib compilations, decrees, teaching materials, and related publications) with purposive and snowball sampling. Data were analyzed using reflexive thematic analysis with source and method triangulation. The findings show that the continuity of the tariqah is maintained through the expansion of functional authority: appointed coordinators and representatives mediate bay’ah, ritual discipline (including qada’), and ethical guidance, without claiming themselves as autonomous murshids. Core practices are carried out in daily and weekly cycles, including congregational Hiziban on Monday night, collective dhikr on Wednesday, and a weekly wazhifah on Friday, and are reinforced by regular muzakarah. Members report increased spiritual awareness, emotional control, and inner tranquility, while also expanding solidarity through infaq and collective work to build madrasah, TPQ, and social services. Historically, the JWK-NW network is reported to have reached around 200,000 members in 1994. This study enriches lived Sufism scholarship by showing a concrete differentiation between spiritual leadership and functional leadership, and it offers the implication that dhikr routines and communal service can become a low-cost infrastructure for character education, youth mentoring, and social cohesion when aligned with local ritual ecology.